Histochemical Evaluation of Mucin-Secreting Cell Activity in the Stomach of the Wistar Rat - Elena HUȚANU; Aurel DAMIAN; Ioana RAȚIU; Vasile RUS; Maria-Cătălina MATEI-LAȚIU; Cristian MARTONOS; Adrian Florin GAL (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine, 2022)
Mucin plays a very important role in the physiological function of the stomach in all species, but the representation of mucin-secreting cells differs from species to species. The aim of this study was to highlight these cells in the stomach of the Wistar rat. For histological investigations, fragments of the stomach from the three main regions (cardiac, fundic and pyloric) were harvested from four Wistar rats and further stained with PAS and Alcian blue methods. The histochemical results showed the presence of mucin-secreting cells in the examined tissues. An intense PAS positive reaction was found in the surface epithelium cells of the gastric mucosa and in the cells lining the gastric crypts in all the three segments. In the deep glandular structures, the cells of the cardiac and fundic glands are PAS negative, while those of the pyloric glands are all PAS positive. For Alcian blue reaction, the cells lining the gastric mucosa and the crypts in the three regions of the stomach were negative. In the glands, the cells of the cardiac and fundic glands were Alcian negative while in the pyloric glands, a limited number of cells arranged in the deep third of the glands showed a weak positive Alcian reaction. In conclusion, the vast majority of glandular cells in the rat's stomach do not synthesize acidic mucins, except for cells in the deep part of the pyloric glands, which synthesize small amounts of such mucins.